Application of micro–meso hierarchical porous carbon for toluene adsorption treatment. (1st July 2016) - Liu, Fang; Yan, Xi; Fan, Fengtao; Zhao, Chaocheng; Liu, Rentao; Gao, Ya; Wang, Yongqiang
Abstract : Organic waste gases from petrochemical industry cause air pollution. Due to the environmental effects of refractory organic gas, the development of effective adsorbent is imperative. The micro–meso hierarchical porous carbon with high surface area was synthesised by the hard‐template method. With MCM‐41 as template, this material was prepared using phenolic resin as carbon source. Dynamic adsorption performance of toluene on micro–meso hierarchical porous carbon was studied by gas chromatographic techniques. Effects of toluene initial concentration, temperature and bed height on adsorption capacity were also researched. The results showed that when toluene concentration was 1750 mg/m 3, equilibrium amount of toluene adsorbed was 358.8 mg/g by micro–meso hierarchical porous carbon, 79.41 mg/g by MCM‐41. The adsorption capacity increased with the increase of initial concentration and bed height, while the adsorption capacity decreased along with the increase of temperature. Due to strong toluene adsorption capacity, this micro–meso hierarchical porous carbon manifests profound theoretical and practical significance in petrochemical organic waste gas treatment.